2002
DOI: 10.1002/gcc.10140
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the minimal region of loss at 13q14 in multiple myeloma

Abstract: Previous studies have focused on the incidence and prognostic implications of 13q14 deletions in multiple myeloma (MM), but none has sought to delineate the minimal common deleted region (CDR). In an effort to do so, dual-color interphase fluorescence in situ hybridization (FISH) was applied on 82 myeloma cases, initially by use of three probes for 13q14 (RB1, D13S319, and D13S25). Deletions were detected in 29/82 (35.4%) cases, and all except one were monoallelic. Subsequently, contiguous YACs, PACs, and a BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 32 publications
1
44
0
1
Order By: Relevance
“…The affected regions are variable and span large portions of 13q, ranging from 13q14 to 13q34. [34][35][36][37] These regions include many expressed sequence tags (ESTs) as well as known genes encoding for transcription factors and cell cycle regulators, such as retinoblastoma (RB1), Kruppel-like factor 12 (KLF12), ret finger protein 2 (RFP2), Drosophila dachshund homo- log 1 (DACH1), deleted in lymphocytic leukemia 1 and 2 (DLEU1 and DLEU2), and glypican 5 (GPC5), a gene with putative roles in the regulation of cell division and growth. 38 However, none of the studies addressing these specific genes have been able to find alterations, other than the monoallelic loss associated with the 13q deletions.…”
Section: Discussionmentioning
confidence: 99%
“…The affected regions are variable and span large portions of 13q, ranging from 13q14 to 13q34. [34][35][36][37] These regions include many expressed sequence tags (ESTs) as well as known genes encoding for transcription factors and cell cycle regulators, such as retinoblastoma (RB1), Kruppel-like factor 12 (KLF12), ret finger protein 2 (RFP2), Drosophila dachshund homo- log 1 (DACH1), deleted in lymphocytic leukemia 1 and 2 (DLEU1 and DLEU2), and glypican 5 (GPC5), a gene with putative roles in the regulation of cell division and growth. 38 However, none of the studies addressing these specific genes have been able to find alterations, other than the monoallelic loss associated with the 13q deletions.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The most frequently deleted genomic region in CLL occurs at chromosome 13q14 and is associated with the indolent form of the disease. 4 The same region is frequently found as the sole cytogenetic abnormality in other types of cancers: 50% of mantle cell lymphomas, 5 B30% of multiple myeloma, 6 and B60% of prostate cancers, 7 indicating that 13q14 contains an important tumor suppressor involved in the pathogenesis of these malignancies. A number of years ago, several laboratories used positional cloning and sequencing of a region of 41 Mb at the deleted region to identify a tumor-suppressor gene at 13q14.…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 99%
“…4 Several authors have reported that chromosome 13 abnormalities indicate an unfavorable prognosis in MM, [5][6][7][8] and various studies have shown that chromosome 13 deletions are early events and represent an adverse prognostic factor in the premalignant condition of monoclonal gammopathies of undetermined significance (MGUS).…”
mentioning
confidence: 99%